2022
DOI: 10.1111/aji.13595
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput analysis of amniotic fluid proteins associated with histological chorioamnionitis in preterm premature rupture of membranes using an antibody‐based microarray

Abstract: Problem To identify potential proteins in the amniotic fluid (AF) that may be associated with histologic chorioamnionitis (HCA) in patients with preterm premature rupture of membranes (PPROM) using antibody‐based microarray analysis. Method of study This was a retrospective cohort study involving 100 singleton pregnant women with PPROM at 24–34 weeks who underwent amniocentesis and delivered within 120 h of amniocentesis. First, the AF proteomes of 15 patients with PPROM and HCA were compared with those of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…50,51 A recent study from our group also showed that TNFR2 levels are significantly elevated in the AF of PPROM women with acute HCA and microbial-associated HCA compared with those without these conditions. 17 Overall, these observations agree with the herein reported TNFR2 data in CVF samples, given the reported association between SPTD risk and acute HCA, and that CVF in PPROM cases may also contain proteins that originate from the AF. 52 In the context of PPROM, the presence of microbial-associated HCA (both HCA and MIAC) represents the worse-case scenario compared with HCA or MIAC alone concerning pregnancy and neonatal outcomes, owing to its strong fetal and intraamniotic inflammatory responses.10-12 Therefore, it is of particular clinical importance to identify patients with PPROM complicated by microbial-associated HCA, preferably based on non-invasive biomarkers, to allow tailoring suitable and timely treatment strategies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…50,51 A recent study from our group also showed that TNFR2 levels are significantly elevated in the AF of PPROM women with acute HCA and microbial-associated HCA compared with those without these conditions. 17 Overall, these observations agree with the herein reported TNFR2 data in CVF samples, given the reported association between SPTD risk and acute HCA, and that CVF in PPROM cases may also contain proteins that originate from the AF. 52 In the context of PPROM, the presence of microbial-associated HCA (both HCA and MIAC) represents the worse-case scenario compared with HCA or MIAC alone concerning pregnancy and neonatal outcomes, owing to its strong fetal and intraamniotic inflammatory responses.10-12 Therefore, it is of particular clinical importance to identify patients with PPROM complicated by microbial-associated HCA, preferably based on non-invasive biomarkers, to allow tailoring suitable and timely treatment strategies.…”
Section: Discussionsupporting
confidence: 92%
“…It is worth noting that, despite these significant relationships, the AUC values of the aforementioned CVF biomarkers ranged within 0.61−0.77, thereby demonstrating poor to fair diagnostic potential for predicting each corresponding endpoint related to acute HCA 46 . Furthermore, some important inflammatory proteins (APRIL, DKK‐3, lipocalin‐2, MIP‐1α, S100A8A9, MMP‐9, VDBP, uPA) were not found to be altered in the CVF of patients with acute HCA or microbial‐associated HCA, whereas previous reports showed that these proteins are elevated in the CVF of women with MIAC/IAI or in the AF of women with acute HCA complicated by PPROM 17,22,23 . These discrepancies can be explained as follows: (i) primarily, HCA‐related inflammation/infection can develop in the interval between CVF sampling and placenta delivery, particularly by an ascending route through the ruptured membranes from the vagina and cervix; (ii) CVF specimens could have been contaminated with vaginal or cervical microbes; thus, inflammatory protein levels measured in the CVF, although it was mixed with AF leaked into vagina, may not completely reflect the inflammatory/infectious state of the amniotic cavity; (iii) early stage ascending intra‐uterine inflammation/infection might be limited to the chorio‐decidua before eliciting inflammatory responses in the amniotic cavity; and (iv) non‐infectious factors, including danger signals, may also contribute to the development of placental inflammation 5 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations